ESTIMASI DAMPAK EKONOMI KONVERSI HUTAN MANGROVE MENJADI PERTAMBAKAN DI DELTA MAHAKAM KABUPATEN KUTAI KARTANEGARA (ESTIMATING OF ECONOMIC IMPACT OF CONVERSION MANGROVE FOREST INTO SHRIMP POND IN MAHAKAM DELTA DISTRICT OF KUTAI KARTANEGARA - Setiawan, Yunianto; Bengen, Dietrich G.; Kusmana, Cecep; Pertiwi, Setyo (Bumi Lestari; Vol 14 No 2 (2014), 2016)
Degradation of mangrove forest in Mahakam Delta were caused by conversion into ponds. These conditions resulted in a decrease in the benefits of the mangrove ecosystem, both directly and indirectly. To restore the environmental conditions, the government rehabilitating ponds by applying sylvofishery pond system. This study aims to estimate the value of externalities mangrove areas converted to ponds in the Mahakam Delta and counting analysis further aquaculture with traditional extensive system as well as sylvofishery system. From the result of study, it can be concluded that value of the lost benefits that reach Rp. 137,484,760,721, - / year of mangrove forests that  have been converted to ponds for  75,311 ha. NVP value was negative and BCR less than 1 for traditional extensive pond system which means that the use of ponds with extensive traditional system will suffer a loss and this business was not feasible at this time as well as the positive value of BCR and NVP more than1 for the sylvofishery pond system means that utilization of ponds with sylvofishery system will be profitable and feasible at this time
Keywords: traditional extensive pond system, sylvofisheri pond system,NPV,BCR